Investigating innovative agroecological approaches for a more sustainable rice production system in Santa Catarina, Brazil. - Verdi, Rovier (2022)
In many ways, agriculture is at the heart of one of the most significant challenges of this century: how to meet the enormous nutritional needs of the growing world population while simultaneously repairing the damage done to the environment due to agricultural activity. Rice farming is particularly relevant in this respect since it contributes significantly to the world's food supply whilst holding much potential for improvement regarding various environmental aspects associated with rice farming systems, especially flooded rice cultivation systems. There are several critical concerns regarding the sustainability of rice cropping systems in the future because the increase in rice production generated by the Green Revolution occurred at the cost of land degradation, salinization of irrigated areas, over-extraction of groundwater, the build up of pest resistance, and damage to the wider environment, such as greenhouse gas emissions and nitrate pollution in water bodies. Alternative solutions to these problems can be found in agroecological approaches, which utilize the genetic and biological potential currently available in crops as well as in soils. The overall purpose of this research was to contribute to improving the state of knowledge on sustainable rice crop systems, specifically regarding the application of innovative and promising agroecological approaches within the Brazilian context, providing useful results to develop further economic, productive, or environmental evaluations and making the transitions to more sustainable agriculture less uncertain. A Participatory Action Research (PAR) approach was used in this study. During the research process, mixed methods were employed, combining research styles from the social and natural sciences. This research is characterized by a spiral of cycles, each cycle consisting of four phases: plan, act, observer, and reflect. In total, this research had 4 research cycles. It started investigating the use of homeopathy as a tool for sustainable rice production in Brazil (cycle 1). This research cycle led to research cycles 2 (a) and 2 (b). In research cycle 2 (a) it was investigated the effects of homeopathic preparation on rice seedlings in a lab experiment in the UK. During research cycle 2 (b), the applicability of the System of Rice Intensification in the Brazilian local context was investigated. This was followed by research cycle 3 where it was investigated the Natural Rice Farming system in the local context. Using a Participatory Action Research (PAR) approach between farmer-technician-researchers and a combination of natural and social science research styles, this pioneering study has made an original contribution to knowledge about sustainable rice production, especially regarding the application of the three innovative agroecological approaches investigated in the Brazilian context. This research has explored the principles, practices, innovative aspects, performance, and main factors affecting innovative 12 agroecological approaches which are at the early stage of development in the Brazilian rice sector. It has provided several original insights into innovative agroecological approaches that demand further exploration of their potential to contribute to the radical transformation of rice production that is necessary both today and in the future